An Early Hands-On Introduction To Grossing And Frozen Section Technique For First-Year Residents. (28th October 2020) - Owczarczyk, A B; Toth, N; Skala, S L
Abstract: Introduction/Objective: First-year pathology residents begin their training with variable experience in anatomic pathology. At the University of Michigan, we have recently instated an introductory rotation ("Introduction to Surgical Pathology" [ISP]) all new residents experience prior to their core surgical pathology rotations. Methods: For the first two weeks of ISP, residents learn to gross under the supervision of certified Pathologists' Assistants. Residents gross biopsies to gain familiarity with dictation and grossing software prior to learning how to approach larger resections. Specific feedback about the content and organization of gross descriptions is provided by the rotation director, and residents are encouraged to review slides from complex specimens they grossed. After orientation, including a lab tour and simulated frozen sections, residents spend two weeks on-service learning to triage specimens (including breast resections and lymphoma work-ups), prepare and cut frozen sections, and participate in frozen reporting. We analyzed the effect of the experience on 8 residents with a 14-question (multiple choice and short answer) pre- and post-rotation quiz and through review of anonymous feedback. Results: Overall, 7/8 residents improved on the post quiz, while one resident's performance slightly decreased. Average scores improved by 5.1 (of 36) points or 14.2%. Scores markedly improved on questions related to cold ischemia time, lymphoma protocol, and frozen section documentation (1–4 residents correct pre- to all correct post- rotation). Residents had difficulty answering questions related to appropriate frozen section requests and mandatory specimen photography, but reported feeling somewhat confident about their ability to gross and to prepare frozen sections. Feedback revealed an appreciation of rotation organization, clear expectations, frozen section simulation, and rotation director availability for feedback and questions. Conclusion: Overall, ISP is a subjectively and objectively valuable rotation. The quiz results and resident feedback have highlighted areas for future improvement, including more effective education about the role of frozen section in surgical management.